Filsafat Dan Jiwa Pendidikan Dalam Perspektif Tiga Ulama Besar : Tradisional, Modern, Dan Integritas - Salsabila Nurhasanah; Nur Hidayahtul Wakhidah; Aminatul Mukhlisa; Prof. Dr. H. M. Yunus Abu Bakar, M. Ag (JOURNAL SAINS STUDENT RESEARCH, 2026)
This article comprehensively examines the educational thought and spirit of three prominent figures of Indonesian Islam—KH. Hasyim Asy’ari, KH. Ahmad Dahlan, and KH. Imam Zarkasyi—who represent three educational paradigms: traditional, modern, and integrative. Using a qualitative research method with a library research approach, this study explores their brief biographies, philosophies, values, and the educational spirit, including the philosophical foundations underpinning the systems each figure developed. The analysis shows that the development of Islamic education in Indonesia is the result of dynamic interaction among these three paradigms, which complement and strengthen one another. This research emphasizes the importance of synthesizing their thoughts in formulating a relevant direction for contemporary Islamic education.